Electromyographic validation of the pectoralis major and deltoideus anterior muscles in inverted fyling exercises with loads - Rodrigues, José Antonio; Büll, M. L. [UNESP]; Dias, G. A R [UNESP]; Gonçalves, M. [UNESP]; Guazzelli, J. F. [UNESP] (My University, 2005)
Inverted flying exercise with external loads of 25, 50, 75 and 100% of each individual maximum load in the pectoralis major and deltoideus anterior muscles was electromyographically analyzed in eleven male volunteers, using surface electrodes MEDI-TRACE-200 connected to a biological signals acquisition module coupled to a PC/AT computer. Electromyographic signals were processed and the effective values obtained were standardized through maximum voluntary isometric contraction. When the concentric phase of each muscle with the same load was statistically compared with the eccentric phase, it was observed that for all loads all the muscles presented significant electromyographic difference, and that the concentric phase was always higher. By analyzing the different loads for each muscle, it was noticed that in the concentric phase all the muscles presented significant electromyographic activity, being it higher with maximum load. When the effect of each load on different muscle in the concentric and eccentric phases was analyzed, the muscles presented a distinct activity profile.
Keywords: Electromyography; Exercises; M. deltoideus anterior; M. pectoralis major; Physical conditioning; adult; concentric muscle contraction; deltoid muscle; eccentric muscle contraction; electromyography; exercise test; functional assessment; human; human experiment; loading test; male; muscle isometric contraction; normal human; pectoralis major muscle; signal detection; statistical analysis; temperature acclimatization; Adolescent; Adult; Exertion; Humans; Male; Muscle Contraction; Pectoralis Muscles; Reference Values; Reproducibility of Results; Shoulder; Supine Position; Weight Lifting